2015
DOI: 10.1007/s00737-015-0501-8
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive coping mediates the influence of childhood trauma on depression and PTSD among pregnant women in South Africa

Abstract: Antenatal mental disorders compromise maternal and child health, and women who have experienced childhood trauma may be at increased risk for such disorders. One hypothesis is that early trauma leads to the development and use of maladaptive coping strategies as an adult, which in turn could predict mental health difficulties during stressful transitions such as pregnancy. To test this hypothesis, this study examined the relationship between childhood trauma and mental health (depression, PTSD) in a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 60 publications
7
33
1
Order By: Relevance
“…Given that maladaptive coping was a potential mediator between stress (e.g., family stress, childhood trauma, and daily hassles) and its psychological and behavioral outcomes including depression, PTSD, and internet addiction (Choi et al, 2015; Ye and Zheng, 2016), it is not strange that we found that OGA were affected by stressful life events indirectly through ACSs (e.g., self-blame, fantasy, withdrawal or rationalization) rather than stressful life events directly.…”
Section: Discussionmentioning
confidence: 99%
“…Given that maladaptive coping was a potential mediator between stress (e.g., family stress, childhood trauma, and daily hassles) and its psychological and behavioral outcomes including depression, PTSD, and internet addiction (Choi et al, 2015; Ye and Zheng, 2016), it is not strange that we found that OGA were affected by stressful life events indirectly through ACSs (e.g., self-blame, fantasy, withdrawal or rationalization) rather than stressful life events directly.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, the diagnostic prevalence of perinatal anxiety disorders range between 3% and 30% for PTSD (Spies et al 2009; Choi et al 2015), 1.5% for panic disorder, 2.3% for phobia and 0.8% for social phobia (Spies et al 2009). Much of the existing research is focused on trauma and stressor-related disorders, and may be specific to the South African context, where there is frequent exposure to community and interpersonal violence or gender-based violence and trauma (Dunkle et al 2004; Myer et al 2008b; Troeman et al 2011; Mahenge et al 2013; Kastello et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the existing research is focused on trauma and stressor-related disorders, and may be specific to the South African context, where there is frequent exposure to community and interpersonal violence or gender-based violence and trauma (Dunkle et al 2004; Myer et al 2008b; Troeman et al 2011; Mahenge et al 2013; Kastello et al 2015). A history of childhood trauma and abuse (Choi et al 2015) and exposure to intimate partner violence (IPV) (Hartley et al 2011) significantly increase the vulnerability for antenatal PTSD, especially in contexts where there are numerous stressors such as poverty, community-based violence and HIV (Shisana et al 2010; Shisana et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Coping behaviors are believed to act as mediators in the relation between the experience of stress and an individual's emotional outcome (Lazarus, 1999). Previous research has found avoidant coping strategies (e.g., denial and mental or behavioral disengagement) to mediate the relation between victimization (i.e., childhood abuse and intimate partner violence) and psychological distress (Calvete, Corral, & Estevez, 2008; Choi et al, 2015; Johnson & Kenkel, 1991; Min et al, 2007). Therefore, we propose a model wherein CSA elicits traumatic stress that is temporarily alleviated through self-medication, and wherein this maladaptive coping strategy leads to poor trauma resolution and ultimately depressive symptomology.…”
mentioning
confidence: 99%